Occurrence of death and stroke in patients in 47 countries 1 year after presenting with atrial fibrillation: a cohort study - Healey, Jeff S; Oldgren, Jonas; Ezekowitz, Michael; Zhu, Jun; Pais, Prem; Wang, Jia; Commerford, Patrick; Jansky, Petr; Avezum, Alvaro; Sigamani, Alben; Demasceno, Albertino; Reilly, Paul; et al. (Lancet, 2016)
BACKGROUND: Atrial fibrillation is an important cause of morbidity and mortality worldwide, but scant data are available for long-term outcomes in individuals outside North America or Europe, especially in primary care settings. METHODS: We did a cohort study using a prospective registry of patients in 47 countries who presented to a hospital emergency department with atrial fibrillation or atrial flutter as a primary or secondary diagnosis. 15 400 individuals were enrolled to determine the occurrence of death and strokes (the primary outcomes) in this cohort over eight geographical regions (North America, western Europe, and Australia; South America; eastern Europe; the Middle East and Mediterranean crescent; sub-Saharan Africa; India; China; and southeast Asia) 1 year after attending the emergency department. Patients from North America, western Europe, and Australia were used as the reference population, and compared with patients from the other seven regions FINDINGS: Between Dec 24, 2007, and Oct 21, 2011, we enrolled 15 400 individuals to the registry. Follow-up was complete for 15 361 (99·7%), of whom 1758 (11%) died within 1 year. Fewer deaths occurred among patients presenting to the emergency department with a primary diagnosis of atrial fibrillation compared with patients who had atrial fibrillation as a secondary diagnosis (377 [6%] of 6825 patients vs 1381 [16%] of 8536, p<0·0001). Twice as many patients had died by 1 year in South America (192 [17%] of 1132) and Africa (225 [20%] of 1137) compared with North America, western Europe, and Australia (366 [10%] of 3800, p<0·0001). Heart failure was the most common cause of death (519 [30%] of 1758); stroke caused 148 (8%) deaths. 604 (4%) of 15361 patients had had a stroke by 1 year; 170 (3%) of 6825 for whom atrial fibrillation was a primary diagnosis and 434 (5%) of 8536 for whom it was a secondary diagnosis (p<0·0001). The highest number of strokes occurred in patients in Africa (89 [8%] of 1137), China (143 [7%] of 2023), and southeast Asia (88 [7%] of 1331) and the lowest occurred in India (20 [<1%] of 2536). 94 (3%) of 3800 patients in North America, western Europe, and Australia had a stroke. INTERPRETATION: Marked unexplained inter-regional variations in the occurrence of stroke and mortality suggest that factors other than clinical variables might be important. Prevention of death from heart failure should be a major priority in the treatment of atrial fibrillation. FUNDING: Boehringer Ingelheim.
Keywords: Humans; lidé; Global Health; smrt; incidence; Female; celosvětové zdraví; Cohort Studies; Incidence; lidé středního věku; Stroke; Comorbidity; Male; komorbidita; Death; Adult; cévní mozková příhoda; dospělí; Atrial Fibrillation; senioři; Aged; fibrilace síní; Middle Aged; ženské pohlaví; mužské pohlaví; kohortové studie